Commuter Choices and Prospects for Improved Urban Mobility - Mandyanda, Aviwe (UNIVERSITY OF WITWATERSRAND FACULTY OF ENGINEERING & THE BUILT ENVIRONMENT, 2016)
The purpose of the study is to understand the everyday social and spatial practices that affect transportation choices in the city from the perspective of public transport commuters. My research is a qualitative inquiry of commuter mobility choices and particularly the reasons behind them. In the pursuit to better understand how transport in South Africa can become more efficient in providing improved levels of access and mobility to a wider spectrum of people, my research focuses on contributing to an understanding of how and why people make individual travel decisions. It investigates how people are responding to the increasing public transportation options and aims to gain a deeper understanding of commuter choices concerning accessibility and mobility in Johannesburg. Drawing from theoretical writings on urban mobility and travel behaviours the main argument of my study is that commuter choices between different modes of transport are influenced by both various socio-economic, spatial and cultural factors, which are attached to practices, narratives and meanings. My study focuses on two transport modes operating along the Johannesburg – Soweto corridor within metropolitan Johannesburg: the Rea Vaya Bus Rapid Transport (BRT) system and the Minibus Taxis (MBTs). It investigates how the two systems have addressed commuter mobility needs, and how commuters are responding to the increased transport options that have become available to them along this corridor. Based on semi-structured interviews, imagery, literature and detailed descriptions emanating from fieldwork, this research report presents everyday life in Pimville as a negotiation and displays the MBT and BRT stations and their users as active participants in this negotiation. The different themes present the different forms of commuter life as negotiation in Pimville.
Investigating BRT and Mini Bus Taxi in Pimville, Soweto
Honours Research Report 2016